Penyuluhan Pemberian Makanan Pendamping ASI Yang Tepat Untuk Pencegahan Stunting di Desa Sayutan Magetan - Achmad Vindo Galaresa; Sesaria Betty Mulyati (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Stunting is a problem of chronic malnutrition due to a lack of nutrition for a long time, resulting in disturbances in children. The impact of stunting is an increase in morbidity and mortality, problems with child development, hindering economic growth and productivity. One of the efforts made to prevent stunting is health counseling to mothers of toddlers, regarding giving MP-ASI to prevent stunting. The results of the evaluation of the implementation of community service activities can run well and are in accordance with the targets. The expected output in this community service can be achieved with an indicator of increasing the level of knowledge of mothers under five about giving MP-ASI as a stunting prevention.